IBM SPSS statistics 27 step by step a simple guide and reference - George, Darren; Mallery, Paul 1966- (Routledge, 2022)
IBM SPSS Statistics 27 Step by Step takes a straightforward, step-by-step approach that makes SPSS software clear to beginners and experienced researchers alike. Extensive use of four-color screen shots, clear writing, and step-by-step boxes guide readers through the program. Output for each procedure is explained and illustrated, and every output term is defined. New to this edition: -Full coverage of the 11 new procedures for power analysis -Effect sizes included throughout Bubble charts in chapter 5 -Bayesian statistics.